Pharmacological Approaches to Colic Pain: Mechanistic Insights and Clinical Evidence on Camylofin-Diclofenac Therapy - Archna Khurana; Devesh Kumar (International Journal of Nursing Research, 2025)
Colic pain, often characterized by intermittent abdominal cramps due to smooth muscle contractions, is a common symptom of various gastrointestinal (GI) disorders such as irritable bowel syndrome (IBS) and functional abdominal pain. Effective management typically involves pharmacological therapies targeting either muscle spasm or inflammation. Camylofin, an antispasmodic, and Diclofenac, a nonsteroidal antiinflammatory drug, represent two key classes of drugs utilized in colic pain management. Camylofin works by blocking calcium ion influx and inhibiting muscarinic receptors, reducing smooth muscle spasms. Diclofenac, through the inhibition of cyclooxygenase enzymes, reduces prostaglandin production, alleviating pain and inflammation. Combining these drugs targets both the muscular and inflammatory components of colic pain, potentially offering a more comprehensive approach to symptom relief. Clinical evidence suggests that the Camylofin-Diclofenac combination is effective in reducing pain and improving quality of life in patients with colic-related disorders, including IBS. While the therapy demonstrates a favorable safety profile in the short term, potential risks such as GI, renal, and cardiovascular side effects should be carefully considered, especially with prolonged use. Further research is required to optimize dosing regimens, evaluate long-term safety, and explore personalized treatment strategies. This review aims to provide a comprehensive overview of the mechanistic insights and clinical evidence supporting the use of Camylofin-Diclofenac combination therapy in managing colic pain.